Evolving Chemotherapy Options for the Treatment of Myeloma Kidney: A 40-Year Perspective - Kastritis, E.; Dimopoulos, M.A.; Bladé, J. (Advances in Chronic Kidney Disease, 2012)
Kidney impairment (KI) at the time of initial diagnosis is common in myeloma. The improvement of kidney function and the reversal of KI are of utmost importance. Recent advances have made it possible to reverse acute kidney damage due to myeloma in most patients, at least if treatment is immediately implemented. Immediate antimyeloma therapy and appropriate hydration are the most commonly used treatment modalities for the management of acute KI related to myeloma. Mechanical approaches can only temporarily reduce the free light-chain load, and without effective chemotherapy they are probably not able to significantly improve kidney function. However, the role of mechanical approaches together with effective chemotherapy is still being explored. Thalidomide, lenalidomide, and bortezomib have improved the survival of myeloma patients, but they have also improved the outcome of patients presenting with KI. Thalidomide is safe to use on patients with KI without dose adjustments. Lenalidomide needs dose modification, but it can improve kidney function in many patients. Bortezomib seems to be the agent of choice for most patients presenting with KI without dose modifications. This review focuses on the management of patients presenting with "myeloma kidney" using modern chemotherapy approaches, especially novel agents. © 2012 National Kidney Foundation, Inc.
Keywords: bortezomib; Creatinine; Dexamethasone; Lenalidomide; Thalidomide